2013
DOI: 10.3389/fncom.2013.00186
|View full text |Cite
|
Sign up to set email alerts
|

Effort minimization and synergistic muscle recruitment for three-dimensional force generation

Abstract: To generate a force at the hand in a given spatial direction and with a given magnitude the central nervous system (CNS) has to coordinate the recruitment of many muscles. Because of the redundancy in the musculoskeletal system, the CNS can choose one of infinitely many possible muscle activation patterns which generate the same force. What strategies and constraints underlie such selection is an open issue. The CNS might optimize a performance criterion, such as accuracy or effort. Moreover, the CNS might sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 56 publications
5
41
2
Order By: Relevance
“…Our results using synergies to improve estimations of muscle activation during gait contrasts with previous studies (Borzelli et al, 2013;Walter et al, 2014;Meyer et al, 2016;Serrancolí et al, 2016) which found generally good estimation of EMG with synergies. The differences between the previous work and our results here broadly fit into three categories: the optimization criteria, the challenge of relating EMG amplitudes to neural excitations, and generic musculoskeletal properties.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results using synergies to improve estimations of muscle activation during gait contrasts with previous studies (Borzelli et al, 2013;Walter et al, 2014;Meyer et al, 2016;Serrancolí et al, 2016) which found generally good estimation of EMG with synergies. The differences between the previous work and our results here broadly fit into three categories: the optimization criteria, the challenge of relating EMG amplitudes to neural excitations, and generic musculoskeletal properties.…”
Section: Discussioncontrasting
confidence: 99%
“…In the prior studies of Walter et al (2014), Meyer et al (2016), and Serrancolí et al (2016), EMG shape tracking was used as part of the optimization algorithm. In this study, we sought to model muscle activations through a modified SO cost function which minimized synergy activations squared, consistent with the optimization previously implemented by McKay and Ting (2012) and Borzelli et al (2013). This cost was motivated by the traditional physiologically motivated cost functions which seek to minimize fatigue or load in individual muscles (Crowninshield and Brand, 1981;Anderson and Pandy, 2001;Ackermann and Van Den Bogert, 2010), while constraining the space of allowable muscle activations to specified patterns FIGURE 6 | Increased sum of muscle stresses for SynSO: Muscle stress measured as the muscle activations squared increased for both TD and CP across all number of synergies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this result, Borzelli et al (2013) suggest that the central nervous system generates forces at the hand by recruitment of muscle synergies rather than by recruitment of individual muscles. Their synergy-based calculation, however, is based on synergies extracted from measured EMG and uses the EMG-based muscle weightings as an input while calculating the activation patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Hardyck and his colleagues were the first practitioners to apply the EMG. 3 In the early 80's Cram and Steger introduced a clinical method for scanning a variety of muscles using sensitive EMG device. 4 It was not until the middle of the 80's, when electrode techniques were integrated, which had a technological level sufficient for the production of small and low weight instrumentation.…”
Section: Introductionmentioning
confidence: 99%